Análisis del clima laboral y cultura organizacional en el ingenio azucarero del norte compañía de economía mixta, Ibarra 2023-2024 - Ruiz Sánchez, Ana Belén (2023)
The objective of this research is to measure the work environment and evaluate the organizational culture of the Ingenio Azucarero del Norte\; whose organization has 293 collaborators, of which 63 are administrative personnel and 230 work in the production area. For the development of the work environment research, the questionnaire (Likert type) proposed by Bizneo (2022) was considered, which includes 14 dimensions. The evaluation of the organizational culture was carried out by applying the Denison Organizational Culture Survey questionnaire designed by Daniel Denison from the University of Michigan. These instruments were applied to all employees of the Mill. The results obtained indicate that the work environment has a positive perception according to 76% of those surveyed. When evaluating the organizational culture, it was determined that the entrepreneurial culture prevails. The results obtained indicate that the work environment of the company has a favorable perception, but with factors that require improvement such as development, ergonomics and facilities, and the culture that predominates is the entrepreneurial type. Finally, strategies are proposed to improve these factors and to maintain an organizational culture according to business requirements.